A Systematic Review of Excessive Social Media Use: Has It Really Affected Our Mental Health? - Apriana Rahmawati; Dona Muji Fitriana; Risna Nur Pradany (Universitas Airlangga, 2019)
Introduction: Social media use has been rapidly increasing over the past few years. Research and practice have mostly focused on the positive impacts of social media, intending to understand and support the various opportunities afforded by this particular technology era. However, it is increasingly observable that social media also involves enormous risks for individuals, communities, firms and even for society as a whole. This systematic review aimed to establish the negative impacts on mental health related to the excessive use of social media.Methods: As many as 15 articles were generated from Scopus, ScienceDirect and Ebscohost. The reviewers independently screened the titles and abstracts in addition to assessing the studies. The study design varied in rigorousness over the quantitative as well as qualitative studies.Results: The result for this study are that having an average daily screen time (more than 2 hours a day) is positively associated with social media addiction. Avoidant attachment was associated with more problematic social media use.Conclusion: Avoidant attachment was associated with more problematic social media use. Thus, an abstinence of several days from social media consumption can caused a reduction in perceived stress.